Production Management of Regional Language Broadcast Program 'Nusantara Kini Malam' at Jawa Pos Multimedia TV Jakarta - Lingga, M Lingga Aryo Maeza Hafiz; Krisna Mulawarman (Jogjakarta Communication Conference (JCC), 2024)
The regional language broadcast program